Особенности функциональной морфологии аппарата звукопередачи некоторых бесхвостых амфибий - Солуха, Б.В. (Вестник зоологии, 1975)
The data on the efficiency of sound transmission from various parts of a body to the inner ear are obtained for Hyla arborea L., Rana ridibunda Pall. and Bombina variegata L. Interspecific differences in sound transmission are in a good agreement with peculiarities of the auditory system structure in the above-mentioned species.